2019
DOI: 10.3389/fnins.2019.00965
|View full text |Cite
|
Sign up to set email alerts
|

Brain Networks Underlying Eye’s Pupil Dynamics

Abstract: Phasic changes in eye’s pupil diameter have been repeatedly observed during cognitive, emotional and behavioral activity in mammals. Although pupil diameter is known to be associated with noradrenergic firing in the pontine Locus Coeruleus (LC), thus far the causal chain coupling spontaneous pupil dynamics to specific cortical brain networks remains unknown. In the present study, we acquired steady-state blood oxygenation level-dependent (BOLD) functional magnetic resonance imaging (fMRI) data combined with ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 66 publications
8
53
0
Order By: Relevance
“…Using pupilometry, Schneider et al (2016) found that spontaneous pupil dilations were associated with increased BOLD activity in the salience network, thalamus, and frontoparietal regions, whereas spontaneous pupil constrictions were associated with increased BOLD activity in the visual and sensoriomotor areas. Similarly, several studies have reported a positive correlation between pupil size and the rsfMRI BOLD signal in regions comprising cingulo-opercular, default mode, and fronto-parietal networks and a negative correlation in the visual and sensorimotor regions (Yellin et al, 2015;Breeden et al, 2017;DiNuzzo et al, 2019). To first order, the spatial pattern of correlations observed with pupilometry are roughly consistent with those reported using simultaneous EEG fMRI studies.…”
Section: Temporal Fluctuations In Vigilance During a Scansupporting
confidence: 81%
See 1 more Smart Citation
“…Using pupilometry, Schneider et al (2016) found that spontaneous pupil dilations were associated with increased BOLD activity in the salience network, thalamus, and frontoparietal regions, whereas spontaneous pupil constrictions were associated with increased BOLD activity in the visual and sensoriomotor areas. Similarly, several studies have reported a positive correlation between pupil size and the rsfMRI BOLD signal in regions comprising cingulo-opercular, default mode, and fronto-parietal networks and a negative correlation in the visual and sensorimotor regions (Yellin et al, 2015;Breeden et al, 2017;DiNuzzo et al, 2019). To first order, the spatial pattern of correlations observed with pupilometry are roughly consistent with those reported using simultaneous EEG fMRI studies.…”
Section: Temporal Fluctuations In Vigilance During a Scansupporting
confidence: 81%
“…To first order, the spatial pattern of correlations observed with pupilometry are roughly consistent with those reported using simultaneous EEG fMRI studies. In addition, a positive correlation has been demonstrated between pupil size and BOLD activity in the locus coeruleus (Murphy et al, 2014;DiNuzzo et al, 2019), a nucleus in the brainstem that contains norepinephrine neurons that are thought to modulate pupil size (Joshi et al, 2016).…”
Section: Temporal Fluctuations In Vigilance During a Scanmentioning
confidence: 99%
“…The link between LC-NE activity and arousal is likely relevant for explaining the role of LC-NE in learned behaviors during wakefulness. LC activation tightly correlates with pupil size and arousal level in mice ( Reimer et al, 2016 ; Breton-Provencher and Sur, 2019 ), monkeys ( Joshi et al, 2016 ), and humans ( Murphy et al, 2014 ; Elman et al, 2017 ; DiNuzzo et al, 2019 ). This activity of LC-NE neurons alone is sufficient to promote global arousal in mice, as photo-activation or -inhibition of LC-NE neurons during wakefulness increases or reduces arousal levels, respectively ( Carter et al, 2010 ; Lovett-Barron et al, 2017 ; Breton-Provencher and Sur, 2019 ; Hayat et al, 2020 ).…”
Section: Lc-ne Regulation Of Arousal and Attentionmentioning
confidence: 99%
“…Pupil size positively correlates with BOLD activations in the Locus Coeruleus, thalamus, posterior cingulate cortex, dorsal anterior cingulate and paracingulate cortex, orbitofrontal cortex, and right anterior insular cortex, i.e. in brain regions associated with selective attention, salience, error-detection and decision-making ( Yellin et al., 2015 , DiNuzzo et al., 2019 ).…”
Section: Metadata Specific To Functional Mrimentioning
confidence: 99%